Implantation of a HeartMate 3 ventricular assist device in a 21‐kg pediatric patient with Fontan failure. Issue 12 (10th October 2020) - Ranney, David N.; Habermann, Alyssa C.; Meza, James M.; Turek, Joseph W.; Lodge, Andrew J.; Vesel, Travis P.; Kirmani, Sonya; Schroder, Jacob N.; Andersen, Nicholas D.
Abstract: Aims: The HeartMate 3 (HM3) ventricular assist device (VAD) is gaining popularity in adults due to a favorable risk profile. However, reports of HM3 use in children are limited, potentially due to concerns with device size. Materials and Methods: Here we report the successful use of an HM3‐VAD as a bridge to transplantation in a 21 kg (BSA 0.84), an 8‐year‐old male child with Fontan failure on home inotropes. Results: Urgent VAD implantation was performed. The standard adult sewing ring was used. The tricuspid valve and papillary muscles were completely excised from the ventricular cavity to prevent inflow obstruction. The pump was placed in the left pleural space. Outflow graft and driveline implantation were routine. VAD function appeared excellent with a reduction in Fontan pressures and improved kidney and liver function. Reoperation was required once to rule out tamponade and twice to evacuate a recurrent right hemothorax. The patient was discharged 3 months later in good condition and underwent successful heart transplantation 10 months after VAD placement. Discussion: This report demonstrates the feasibility of HM3‐VAD implantation in a 21‐kg Fontan patient, suggesting HM3 size is not a prohibitive limitation at this weight.